2018
DOI: 10.1002/jlcr.3669
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon‐14 labeled ketamine and norketamine

Abstract: Ketamine is a well-known general anesthetic that inhibits cerebral NMDA receptors. Norketamine is a major circulating metabolite of this drug. A nasal spray formulation of esketamine, the S enantiomer of ketamine, is under development for the management of treatment-resistant depression. To assess the pharmacokinetic properties, C-14 labeled ketamine and norketamine were prepared separately from commercially available [ C]CuCN through a five-step sequence with the C-14 label at the quaternary carbon of the cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Peaks 1 and 3 may have originated from decomposition products of 2‐FDCK. Furthermore, as the content of 2‐fluorodeschlorohydroxylimine (Peak 2) decreased, the signal of 2‐FDCK also weakened rapidly, indicating that 2‐FDCK may not be present in the suspected chemical precursor and probably originated from the thermal rearrangement of 2‐fluorodeschlorohydroxylimine at the high‐temperature inlet of GC–MS 24,38–41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks 1 and 3 may have originated from decomposition products of 2‐FDCK. Furthermore, as the content of 2‐fluorodeschlorohydroxylimine (Peak 2) decreased, the signal of 2‐FDCK also weakened rapidly, indicating that 2‐FDCK may not be present in the suspected chemical precursor and probably originated from the thermal rearrangement of 2‐fluorodeschlorohydroxylimine at the high‐temperature inlet of GC–MS 24,38–41 …”
Section: Resultsmentioning
confidence: 99%
“…In the reproducibility experiment, the integrated areas of the four ingredients in the suspected chemical precursor of 2-FDCK were found to be significantly altered even at short time intervals. In the 25-h continuously monitored experiment, the acetonitrile solution of decreased, the signal of 2-FDCK also weakened rapidly, indicating that 2-FDCK may not be present in the suspected chemical precursor and probably originated from the thermal rearrangement of 2-fluorodeschlorohydroxylimine at the high-temperature inlet of GC-MS. 24,[38][39][40][41] The data in Figure 5 indicate that 2-fuorodeschlorohydroxylimine dissolved in acetonitrile decomposed rapidly at room temperature.…”
Section: Stability Investigation Of 2-fluorodeschlorohydroxyliminementioning
confidence: 99%
“…Although these asymmetric syntheses of ( S )- 1 have achieved some success, each route has limitations on its industrialization. Thus, classical resolution of the inexpensive racemate (±)- 1 with l -(+)-tartaric acid remains the best choice for the industrialization of ( S )- 1 because of its straightforward and commercial scalability (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…An approach appropriate for industrial production to synthesize racemic ketamine 1 was reported in the early 1960s by Stevens that uses 2-chlorophenyl cyclopentyl ketone ( 4 ) as a starting material (Scheme ). The conceptionally elegant synthesis of 1 involves a bromination–imination–thermal rearrangement sequence and was adopted for the preparation of ketamine analogues by the Janssen Pharmaceutical Company in the laboratory . Another economical and environmental procedure for the preparation of racemic ketamine under sustainable continuous flow conditions was reported by Monbaliu in 2019 .…”
Section: Introductionmentioning
confidence: 99%
“…The original synthetic route was reported by Stevens using commercially available ketone 2 as the starting material (Scheme ). This concise procedure includes three steps, bromination, imination, and thermal rearrangement. , However, there are some disadvantages in this route, such as low atomic economy (copper bromide and excessive liquid methylamine) and harsh reaction conditions (−40and 180 °C) recently, Zhang and colleagues reported a new strategy to synthesize (±)- 1 using the uncommercial o -chlorophenyl cyclohexanone as the starting material, which was next subjected to direct nitration utilizing excessive ceric ammonium nitrate ((NH 4 ) 2 Ce­(NO 3 ) 6 ). Unfortunately, the nitration step was conducted in dichloroethane with a low isolated yield (51%) and consequently resulted in an unsatisfactory total yield (25%).…”
Section: Introductionmentioning
confidence: 99%